(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Plyometric training is effective to improve the performance of the athletes by increasing the speed power and ability to do the activity. Most of the recreational athletes have no idea about the proper training in the field and they are very prone to get injury. This study was designed to provide the proper training and prevent further injuries in the athletes. Objectives: To find out the effect of plyometric training on vertical jump height and horizontal jump height in recreational athletes indulging in jumping activities according to age, gender, body mass index and years of playing. Methodology: 61 subjects participated in this study according inclusion and exclusion criteria. Prior consent was taken. Pre and post assessment of the vertical and horizontal jump height was taken. The protocol was for 3 days per week for 6 weeks. Later evaluation and interpretation of data was done. Result: There is significant comparison between the pre and post treatment (p=<0.0001) of horizontal and vertical jump height. Even there is positive correlation of years of playing in week 6(p=0.58) for horizontal jump height and in week 6 (p=0.43) for vertical jump height. There is negative correlation of age in week 6(p=0.002) of horizontal jump height in week 6(p=0.31) of vertical jump height . Conculsion: This study concluded that the effect of plyometric training was seen in recreational atheletes indulging in jumping activities.